2004
DOI: 10.1073/pnas.0405443101
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome healing through terminal deletions generated by de novo telomere additions in Saccharomyces cerevisiae

Abstract: Broken chromosomes healed by de novo addition of a telomere are a major class of genome rearrangements seen in Saccharomyces cerevisiae and similar to rearrangements seen in human tumors. We have analyzed the sequences of 534 independent de novo telomere additions within a 12-kb region of chromosome V. The distribution of events mirrored that of four-base sequences consisting of the GG, GT, and TG dinucleotides, suggesting that de novo telomere additions occur at short regions of homology to the telomerase gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
51
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 77 publications
(133 reference statements)
7
51
0
Order By: Relevance
“…A similar distribution is observed for de novo telomere additions (see Fig. S1 in the supplemental material) that target short TG-rich regions during the healing of broken chromosomes (83).…”
Section: Resultssupporting
confidence: 69%
“…A similar distribution is observed for de novo telomere additions (see Fig. S1 in the supplemental material) that target short TG-rich regions during the healing of broken chromosomes (83).…”
Section: Resultssupporting
confidence: 69%
“…The suppression mechanisms include cell cycle checkpoints [7][8][9][10][11][12], post-replication [13,14] and mismatch repair [15,16], recombination pathways, an anti-de novo telomere addition mechanism [17,18], chromatin assembly factors [11,19], mechanisms that prevent end-to-end chromosome fusions [17,18,20] and a pathway detoxifying reactive oxygen species [14,21,22]. In contrast, the promoters of GCRs include telomerase-related factors [17,23], a mitotic checkpoint network [24], the Rad1-Rad10 endonuclease [25], non-homologous end-joining proteins including Lig4 and Nej1 [17], a pathway generating inappropriate recombination via sumoylation and the Srs2 helicase [13] and the Bre1 ubiquitin ligase [13].…”
Section: Introductionmentioning
confidence: 99%
“…Translocations and other gross chromosomal rearrangements (GCRs), i.e., deletions and inversions, are often observed in cancer cells (6). Recently, seven pathways that suppress (7)(8)(9) and four pathways that are required for the formation of GCRs (10)(11)(12) have been identified in yeast. From the great number and redundancy of factors involved in GCR suppression, it can be concluded that any genomic rearrangement is highly deleterious to cells, and, once escaped from control, it can have a massive impact on cellular morphology and physiology.…”
mentioning
confidence: 99%